Analysis of Phenol Biodegradation in Antibiotic and Heavy Metal Resistant Acinetobacter lwoffii NL1 - Xu, Nan; Qiu, Chong; Yang, Qiyuan; Zhang, Yunzeng; Wang, Mingqi; Ye, Chao; Guo, Minliang (Frontiers in Microbiology, 2021)
Phenol is a common environmental contaminant. The purpose of this study was to isolate phenol-degrading microorganisms from wastewater in the sections of the Chinese Medicine Manufactory. The phenol-degrading Acinetobacter lwoffii NL1 was identified based on a combination of biochemical characteristics and 16S rRNA genes. To analyze the molecular mechanism, the whole genome of A. lwoffii NL1 was sequenced, yielding 3499 genes on one circular chromosome and three plasmids. Enzyme activity analysis showed that A. lwoffii NL1 degraded phenol via the ortho-cleavage rather than the meta-cleavage pathway. Key genes encoding phenol hydroxylase and catechol 1,2-dioxygenase were located on a megaplasmid (pNL1) and were found to be separated by mobile genetic elements; their function was validated by heterologous expression in Escherichia coli and quantitative real-time PCR. A. lwoffii NL1 could degrade 0.5 g/L phenol within 12 h and tolerate a maximum of 1.1 g/L phenol, and showed resistance against multiple antibiotics and heavy metal ions. Overall, this study shows that A. lwoffii NL1 can be potentially used for efficient phenol degradation in heavy metal wastewater treatment.